정수계획법을 활용한 시차를 고려한 온라인 학회 스케줄링 방법 제안 - 이현태; 윤범; 조예림; 이수현; 정슬기 (경영과학, 2023)
In this study, we present a scheduling method for online conferences considering the time difference. Due to COVID-19, many conferences have been held online. At online conferences, presenters give presentations at their original residences. Therefore, it may be necessary to allow presenters to give the presentation during their main activity time if possible. This study proposes a method of scheduling online conferences in consideration of the time difference based on the stream information divided according to research topics. The proposed polynomial time algorithm is divided into two steps. The first step uses a heuristic algorithm for partitioning presentations into sessions, and the second step proposes an integer program to allocate sessions to time slots.
Keywords: Conference Scheduling; Online Conference; Integer Programming; Heuristic Method